Den svensk-nederländska/nederländsk-svenska ordboken. En bidirektionell ordbok i ett dubbelt binationellt perspektiv - Laureys, Godelieve (Nordiske Studier i Leksikografi, 1997)
The Swedish-Dutch/Dutch-Swedish dictiomuy was published at the end of 1996 as a co-production between Van Dale Lexicografi.e (The Netherlands/Belgium) and Norstedts Förlag (Sweden). The dictiomuy was made at the Scandinavian Department at the university of Groningen <luring the period 1990-95. There were both Dutch and Swedish native speakers in the editorial staff. The dictiomuy was conceived as a 'bidirektionell' lexicography instrument, which means that it should be as easy to use for Dutch and Swedish native speakers, and that it contains the same kind ofinformation for both user groups. In my speach I intend to illustrate our ways ofworking that form the basis for this 'bidirektionell' funtion and what kind ofimplications this concept has brought about e.g. the choice ofa metalanguage etc. Another interesting aspect we paid a lot of attention to is the so-called 'binational' perspective. Both Swedish and Dutch happen to be languages that are being spoken in two countries, resp. Sweden/Finland and The Netherlands/Belgium. This implies a specific linguistic method, when handling society words (e.g. (Swe) utbildningsdepartement/(Fin) undervisningsministerium) on the one hand, and so-called provincial words (e.g. sv tvättställ/flsv lavoar; AN wastafel/AZN lavabo) on the other. In this respect the dictiomuy reflects contemporary language norms and focuses on specific attitudes in binational language societies.